To Nap or Not to Nap: Excessive Daytime Napping Is Associated With Elevated Evening Cortisol in Nursing Home Residents With Dementia. (April 2013) - Woods, Diana Lynn; Kim, Haesook; Yefimova, Maria
Background: Alterations in the sleep–wake cycle, including daytime napping, are consistently reported in persons with dementia (PWD). A dysregulation in the hypothalamic–pituitary–adrenal (HPA) axis, indexed by elevated evening cortisol, may offer one explanation for these alterations. Alternatively, excessive daytime sleeping may alter cortisol rhythm and increase intraindividual variability, potentially contributing to increased environmental reactivity and behavioral symptoms. The purpose of this substudy ( N = 12) was to examine the association between daytime napping and basal cortisol diurnal rhythm in nursing home residents with dementia. Method: In this within-individual longitudinal design, saliva samples were obtained daily for 5 consecutive days upon waking and 30–45 min, 6 hr, and 12 hr after waking to obtain a cortisol diurnal rhythm. Behavior and sleep–wake state (nap/no nap) were observed and recorded every 20 min for 12 hr per day for 5 days. Results: Participants were categorized as high nappers (HNs) or low nappers (LNs). There was a significant difference in evening cortisol levels ( t = −2.38, p = .032) and continence ( t = 3.37, p = .007) between groups, with HNs exhibiting higher evening cortisol levels. There were no other significant differences in resident characteristics between the two groups. Conclusions: These data suggest a link between excessive daytime napping and elevated evening cortisol in PWD consistent with findings in children. Elevated evening cortisol is an indication of a dysregulation in the HPA axis. These preliminary data support a close association between the sleep–wake cycle and HPA-axis regulation in PWD.